Prognostic significance of the interval between the initiation of antiretroviral therapy and the initiation of anti‐tuberculosis treatment in HIV/tuberculosis‐coinfected patients: results from the TREAT Asia HIV Observational Database. Issue 2 (28th August 2013) - Han, SH; Zhou, J; Lee, MP; Zhao, H; Chen, Y‐MA; Kumarasamy, N; Pujari, S; Lee, C; Omar, SFS; Ditangco, R; Phanuphak, N; Kiertiburanakul, S; et al.
<x xml:space="preserve">Abstract</x> Objectives We evaluated the effect of the time interval between the initiation of antiretroviral therapy (ART) and the initiation of tuberculosis (TB) treatment on clinical outcomes in HIV/TB‐coinfected patients in an Asian regional cohort. Methods Adult HIV/TB‐coinfected patients in an observational HIV‐infected cohort database who had a known date of ART initiation and a history of TB treatment were eligible for study inclusion. The time interval between the initiation of ART and the initiation of TB treatment was categorized as follows: TB diagnosed while on ART, ART initiated ≤ 90 days after initiation of TB treatment ('early ART'), ART initiated > 90 days after initiation of TB treatment ('delayed ART'), and ART not started. Outcomes were assessed using survival analyses. Results A total of 768 HIV/TB‐coinfected patients were included in this study. The median CD4 T‐cell count at TB diagnosis was 100 [interquartile range (IQR) 40‐208] cells/μL. Treatment outcomes were not significantly different between the groups with early ART and delayed ART initiation. Kaplan−Meier analysis indicated that mortality was highest for those diagnosed with TB while on ART (3.77 deaths per 100 person‐years), and the prognoses of other groups were not different (in deaths per 100 person‐years: 2.12 for early ART, 1.46 for delayed ART, and 2.94 for ART not started). In a multivariate model, the interval between ART initiation and TB therapy initiation did not significantly impact all‐cause mortality. Conclusions A negative impact of delayed ART in patients coinfected with TB was not observed in this observational cohort of moderately to severely immunosuppressed patients. The broader impact of earlier ART initiation in actual clinical practice should be monitored more closely.